The training of social workers. : An analysis of the training projects at the Santa Fe School of Social Service in the long decade of the 1940s (Papeles, 2023)
In this article we analyze the founding mandate and the conflicting projects in the training of Social Assistants in Santa Fe between the '40s and early '50s. For that, we make a brief contextualization of the creation of the School of Social Service, identifying the aspects of the state political-institutional scaffolding in which the first Study Plan of the career is gestated. From a comparative analysis of the Study Plans developed during the period in question, we characterize the main discussions in relation to the professional training of Social Assistants considering internal and external variables of the disciplinary field. From this analysis we conclude that there is a foundational mandate to rationalize and professionalize Assistance as a state policy, the subordination of professional training to the orientation of social policy and the needs of each government to strengthen its ideas. Regarding the training projects, we identified different discourses with foundations ranging from social justice to hygiene, from technique to ethics and commitment, from reason to affection and passion, from knowledge to virtue.
Keywords: Social Work; Professional Formation; Professional Profile; Study Plan; Santa Fe